PENGEMBANGAN BAHAN AJAR PERMAINAN BOLA BESAR SEBAGAI SUMBER BELAJAR DI SMA NEGERI 1 TRIMURJO - Alfayreza Ginantara; Rachmi Marsheilla Aguss (Journal of Physical Education, 2022)
The purpose of this study was to develop, analyze the feasibility and analyze the responses of teachers and students to the developed product. This study uses the ADDIE development model. The test subjects in this study were one teacher and ten students of class X MIA SMA Negeri 1 Trimurjo. The data analysis technique in this research is quantitative and qualitative data analysis. The results of product validation by material experts were carried out three times, obtained a percentage score of 78,75%  (Valid), while the results of  media expert validation were carried out twice, obtained a percentage score of 90% (Very valid). The results of the teacher’s response obtained a percentage score of  85% (Very valid) and the results of student responses obtained a percentage score of 93% (Very valid). Based on the results of the feasibility assesment, the average percentage score was 86,7%, so it can be concluded that the big ball game teaching materials product developed is very suitable for use in physical education.